STATUS KEPEMILIKAN RUMAH SUSUN DI ATAS HAK GUNA BANGUNAN YANG MELEKAT DI ATAS HAK PENGELOLAAN (TANAH KOMPLEK BANDARA KEMAYORAN) - Purbandari Purbandari (UNISSULA, 2014)
Organizers of development (third party) who has entered into an agreement with the holder of rights management; such as rights management is controlled by Indonesian State Secretariat complex on land Kemayoran New Town Airport; may establish flats on land management right after previously completing the status of land rights into Broking . Management Rights is a right that comes from the State of land tenure which authorizes the holder of rights. Management rights will not expired , but Broking attached on it still has a term to be extended with the consent of the owner of the Management. An issue for state ownership apartment units in Bandar Kemayoran New Town when Broking cannot be extended or split Certificate of Ownership Flats Upper Unit not approved by the holders of Rights Management. This study uses a type of juridical normative, descriptive, using a data collection tool to obtain documents study secondary data sourced on primary legal materials, secondary and tertiary units associated with the ownership of the Flats above Broking attached on the Management of New Town Kemayoran Airport, using qualitative analysis.